Adherence to the Mediterranean diet in children: Is it associated with economic cost?. Issue 4 (July 2017) - Albuquerque, G.; Moreira, P.; Rosário, R.; Araújo, A.; Teixeira, V. H.; Lopes, O.; Moreira, A.; Padrão, P.
ABSTRACT : Highlights : The average diet cost was 4.58€ (SD = 1.24) in 6–12 years‐old children. Diet cost calculations were based on food prices information from 2011. Most children reported medium (69.1%) or high (4.6%) adherence to Mediterranean diet. Higher adherence to Mediterranean diet was associated with higher diet cost. Objective: : To assess how the diet cost is associated with socio‐demographic factors and adherence to Mediterranean diet in children. Methods: : Data were obtained from a community‐based survey of children selected from public elementary schools in Portugal. Of a total of 586 children attending these schools, 464 (6–12 years), were studied. Dietary intake was assessed by a 24 hour recall and the adherence to Mediterranean diet was evaluated through the KIDMED index. The cost of the diet was calculated based on the collection of food prices of a national leader supermarket, and expressed as Total Daily Cost (TDC) and Total Daily Cost‐Adjusted for Energy (TDEC). Anthropometric measures were taken and socio‐demographic data were gathered from a questionnaire filled by parents. Logistic regression was used to quantify the association between diet cost, socio‐demographics and adherence to Mediterranean diet. Results: : The average TDC was 4.58€ (SD = 1.24). Most children (69.1%) reported medium adherence to Mediterranean diet, and 4.6% rated the higher score. TDC was higher for children with highest adherence to Mediterranean diet, compared to those with lowest adherence [TDC: OR = 5.70 (95% CI 1.53, 21.33), p for trend = 0.001; TDEC: OR = 2.83 (95% CI 0.89, 8.96, p for trend 0.018)]. No meaningful variation in the diet cost with age and parental education was observed. Conclusion: : Higher adherence to Mediterranean diet was associated with higher diet cost in children.